Effect of Bacterial Distribution and Activity on Conjugal Gene Transfer on the Phylloplane of the Bush Bean (Phaseolus vulgaris) - Normander, Bo (American Society for Microbiology, 1998)
Conjugal plasmid transfer was examined on the phylloplane of bean (Phaseolus vulgaris) and related to the spatial distribution pattern and metabolic activity of the bacteria. The donor (Pseudomonas putida KT2442) harbored a derivative of the TOL plasmid, which conferred kanamycin resistance and had the gfp gene inserted downstream of a lac promoter. A chromosomal insertion of lacI(q) prevented expression of the gfp gene. The recipient (P. putida KT2440) had a chromosomal tetracycline resistance marker. Thus, transconjugants could be enumerated by plating and visualized in situ as green fluorescent cells. Sterile bean seedlings were inoculated with donors and recipients at densities of approximately 10(5) cells per cm(2). To manipulate the density and metabolic activity (measured by incorporation of [(3)H]leucine) of the inoculated bacteria, plants were grown at various relative humidities (RH). At 100% RH, the transconjugants reached a density of 3 × 10(3) CFU/cm(2), corresponding to about one-third of the recipient population. At 25% RH, numbers of transconjugants were below the detection limit. Immediately after inoculation onto the leaves, the per-cell metabolic activity of the inocula increased by up to eight times (100% RH), followed by a decrease to the initial level after 96 h. The metabolic activity of the bacteria was not rate limiting for conjugation, and no correlation between the two parameters was observed. Apparently, leaf exudates insured that the activity of the bacteria was above a threshold value for transfer to occur. Transconjugants were primarily observed in junctures between epidermal cells and in substomatal cavities. The distribution of the transconjugants was similar to the distribution of indigenous bacteria on nonsterile leaves. Compared to polycarbonate filters, with cell densities equal to the overall density on the leaves, transfer ratios on leaves were up to 30 times higher. Thus, aggregation of the bacteria into microhabitats on the phylloplane had a great stimulatory effect on transfer.